Aktivitas Antimikroba Ekstrak Infusa Daun Bakau Rhizopora Sp. Terhadap Bakteri Staphylococcus aureus - Rahmawati Nur Annisa (ACROPORA: Jurnal Ilmu Kelautan dan Perikanan Papua, 2023)
This study aimed to evaluate the potential antimicrobial activity of Rhizophora sp. mangrove leaf infuse extract against Staphylococcus aureus bacteria. S. aureus is a pathogen often associated with human infections, and this research sought to uncover the leaf extract's ability to inhibit the growth of this bacterium. The research method involved the collection of Rhizophora sp. mangrove leaves and the preparation of infuse extract. Subsequently, antimicrobial activity testing was conducted using the disc diffusion method. The research findings showed that the mangrove leaf infuse extract had the capability to create growth inhibition zones in S. aureus cultures, indicating significant antimicrobial activity. The strong range of inhibition zone diameters at a concentration of 100% was 20.41 mm, at 80% concentration was 20.25 mm, and at 60% concentration was 19.33 mm